(untitled) (DIMENSI: Journal of Architecture and Built Environment, 2016)
Environmentally sound approach for sustainable urban drainage could promote infiltration and lower the risk of flooding. This study presents the framework to evaluate the drainage alternatives considering multiple aspects including water quantity, life cycle cost and amenity. This approach is verified through application at a residential area in Malang city Indonesia. Different combinations of drainage components comprising of drainage channels, infiltration wells and biopore absorption holes are assessed regarding runoff reduction, present value of life cycle cost, and willingness to pay for the convenience. The first part describes the effective designs of sustainable drainage components in the houses as well as in the public spaces of the housing. The second part of this study describes the use of analytic hierarchy process for weight assignment of sustainability criteria and multiple benefit calculation. The study recommends infiltration wells and biopore absorption holes together with drainage channels as the best management practice of sustainable drainage system based on its overall sustainability index.